Voces en el silencio - Ormeño Castro, Javier Alfonso (2023)
This paper explores the effects of hospitality rites and the co-creation of common spaces as a means to achieve transitional justice in Peru, 20 years after the 1980–⁠2000 internal armed conflict. It describes a tea ceremony in La Hoyada, a place used by the Army as a clandestine burial ground. A foreign act of hospitality breaks the temporality of the site; mindful actions create silence, and the voices of people are better heard. This work describes the development of an incipient methodology, an intimate language of presence, and how video recordings of participants’ testimonies captured the feelings arising in a one-time silent event.